Adding anaerobic digestate to commercial farm fields increases soil organic carbon - Villarino, Sebastián Horacio (2025)
Integrating anaerobic digestion technology canhelp farms meet agronomic, environmental, and economic goals. The slurryby-product from anaerobic digestion – anaerobic digestate – can be applied to croplands as an organicamendment and fertilizer. However, digestate effects on soil organic carbon(SOC) and soil fertility are poorly understood, especially at the field scale.In this study, we analyzed data from a multi-fieldcommercial farm in Iowa, USA, which integrates agricultural production withanaerobic digestion. The digestate produced in this system was applied to14 crop fields over 5-12 years. To assess the digestate effects on SOC stocksand soil plant-available nutrients, we analyzed the digestate chemicalcomposition, digestate rates, and soil test results of 421 samples taken at0-15 cm soil depth. Most sampled points (86%) increasedSOC stock, with greater gains observed in soilswith lower initial SOC levels. The average SOC accrual rate was 0.8 Mg ha-1y-1 (confidence interval: 0.7-0.9 Mg ha-1 yr-1),and isotope analysis (13C and 15N)indicated that new soil organic matter is primarily derived from digestate. Assumingsimplified SOC dynamics, the SOC formation efficiencyfrom digestate was estimated at 18% (higher than the estimate for raw manure).Anaerobic digestate also increased soil test phosphorus (STP) and potassium,with STP values doubling over eight years, exceeding crop requirements.Integrating anaerobic digestion on farms can help reverse soil degradation andenhance agricultural sustainability, although STP should be monitored toprevent potential adverse environmental impacts.